2004
DOI: 10.2307/4128775
|View full text |Cite
|
Sign up to set email alerts
|

"Sturdy Black Bridges": Discussing Race, Class, and Gender

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The chapters in Part Two, "Toward a New Perspective: Learning to Interpret Culturally Diverse Literature," offer insight on some of the nuances of particular cultural groups' literary traditions, with suggestions as to how multicultural texts might be taught, evaluated, and appreciated from the perspectives of the cultural group depicted in them. Because of my own work-which involves the intertexual relationships between AAYA (African American Young Adult) literature by women, literature within the broader African American women's literary tradition written largely for an adult audience, and black feminist theory-I was particularly drawn to chapters such as Richard Van Dongen's and Lingyan Yang and Zhihui Fang's (Hinton-Johnson, 2003;Hinton, 2004). Dongen argues that, as a cultural outsider, he reads books by and about Hispanics multiculturally by examining his own assumptions and expectations concerning the elements of literature coupled with his knowledge of aspects of Hispanic cultural traditions, including folklore.…”
Section: Exploring Culturally Diverse Literature For Children and Adomentioning
confidence: 99%
“…The chapters in Part Two, "Toward a New Perspective: Learning to Interpret Culturally Diverse Literature," offer insight on some of the nuances of particular cultural groups' literary traditions, with suggestions as to how multicultural texts might be taught, evaluated, and appreciated from the perspectives of the cultural group depicted in them. Because of my own work-which involves the intertexual relationships between AAYA (African American Young Adult) literature by women, literature within the broader African American women's literary tradition written largely for an adult audience, and black feminist theory-I was particularly drawn to chapters such as Richard Van Dongen's and Lingyan Yang and Zhihui Fang's (Hinton-Johnson, 2003;Hinton, 2004). Dongen argues that, as a cultural outsider, he reads books by and about Hispanics multiculturally by examining his own assumptions and expectations concerning the elements of literature coupled with his knowledge of aspects of Hispanic cultural traditions, including folklore.…”
Section: Exploring Culturally Diverse Literature For Children and Adomentioning
confidence: 99%
“…Recent studies that critique representation of occupations or positions (McElhoe, 1999), gender (Marshall, 2004;Roberts & Hill, 2003;Vallone, 2002), and race (Hinton, 2004;Nilsson, 2005) suggest that picture books influence the way that readers read. Such awareness can lead to educators being conscious of bringing in a wider range of texts that render culture in more complex ways.…”
Section: Reading Codes: Implications For Research and Practicementioning
confidence: 99%
“…Research has shown that longer works, including novels and chapter books, can effectively generate critical conversations, especially with adolescent readers (Batchelor et al, 2018; Hinton, 2004; Schieble, 2012). However, our experiences have affirmed the value of the unique affordances of picturebooks in creating spaces for topical discussions suitable and developmentally appropriate for a wide range of audiences.…”
mentioning
confidence: 99%